Central Composite Design (CCD) and Box-Behnken Design (BBD) for the Optimization of a Molecularly Imprinted Polymer (MIP) Based Pipette Tip Micro-Solid Phase Extraction (SPE) for the Spectrophotometric Determination of Chlorpyrifos in Food and Juice. (13th October 2022) - Tamandani, Mahsa; Hashemi, Sayyed Hossein
Abstract: A novel micro-solid phase extraction protocol based on a new molecularly imprinted polymer (MIP) sorbent is reported for the isolation of chlorpyrifos from rice, juice and fish samples followed by spectrophotometric determination. The MIP sorbent was packed into a pipette tip. The type and volume of the eluent, pH, mass of MIP, sample volume, and number of extraction and elution cycles were evaluated utilizing a one-variable-at-a-time protocol, central composite design, and Box-Behnken design. The results demonstrated the optimum performance of central composite design. The linear range under the optimal conditions for chlorpyrifos was from 1 to 1000 µg L −1 with a limit of detection of 0.17 µg L −1 and a relative standard deviation less than 4.3%. The protocol was successfully employed for the determination of trace concentrations of chlorpyrifos in fish, juice, and rice.